THE EFFECT OF SERVICE QUALITY ON THE HOSPITAL IMAGE IN BATAM - Hajan Hidayat; Rizki Syafitri Lubis (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
The aims of this research to examine the effect of service quality on the hospital image in Batam through customer satisfaction as an intervening variable. Service quality was measured by quality dimensions namely: tangibles, reliability, responsiveness, empathy, and assurance. Sampling method in this research using purposive sampling. Research objects is one public hospital and one private hospital in Batam with 196 sample respondents. The results of this research showed that service quality has a significant impact on hospital image through customer satisfaction as an intervening variable. Limitations of this research are the respondents only from the patients or visitors and only use one private hospital and one public hospital. Implications obtained in this research that service quality is good or bad will affect to customer satisfaction and it will be affect to image or impression of the customers toward hospital. The future studies may added samples not only in hospital but in other health care also.